Teollinen kulttuuriperintö vakiintui suomalaiseen historiatietoisuuteen - Anna Sivula (Tekniikan historian seura, 2025)
<!--[if gte mso 9]> <![endif]-->
The cultural heritage value is based on history. Industrial heritage is a relatively young phenomenon in Finland. It emerged in late the 1970s. The concepts, definitions and practice of industrial heritage, were adopted to Finland from Sweden. The first industrial heritage sites were proto-industrial ironworks, but during the late 1970’s and early 1980’s the factories and industrial landscapes were included in the definition. The area covered by the concept was expanded in the 1980s. The oral traditions of the working class dominated the field of the intangible industrial cultural heritage for a couple of decades. Today, the concept of industrial heritage covers many different perspectives. It took three decades to integrate the consciousness of industrial heritage into the Finnish history culture. The Finnish key concepts of the Industrial Heritage were coined as late as in the early 2000’s. The terminology was finally clarified in international discussions and seminars, written and held in English.
<!--[if gte mso 9]> Normal 0 21 false false false FI X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US;} --><!--[endif] -->